La puerta - Taller de cine UNL (Taller de cine UNL, 2020)
Con: Carolina Cano, Julia Deré, Betina Deré. Participan: Nora Tardivo, Miguel Mércuri, Leonardo Rusillo, Betsy Salva, Magdalena Molina, Gustavo Durando. Música: “Vistiendo”, de Gabriel Ruiz Díaz, Catupecu Machu. Jefe de eléctricos: Marisel Gruber.